Relationship between Mother's Knowledge about Exclusive Breastfeeding and Giving MPASI with Stunting Incidence in Children Aged 24-59 Months in Bale Village Working Area of Wani Health Center, Donggala District: Hubungan Pengetahuan Ibu tentang Asi Eksklusif dan Pemberian MPASI dengan Kejadian Stunting pada Anak Usia 24-59 Bulan di Desa Bale Wilayah Kerja Puskesmas Wani Kecamatan Donggala - Nurmalisa, Baiq Emy (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
Stunting is a condition in which toddlers have less length or height when compared to their age. Globally in 2016 as many as 22.9% or around 154.8 million children under five in the world suffer from stunting. The number of stunting cases in toddlers in Bale Village was 58 children. The aim of the study was to find out the relationship between mother's knowledge about exclusive breastfeeding and giving MP-ASI with the incidence of stunting in toddlers aged 24-59 months in Bale Village, working area of ​​the Wani Health Center, Tanantovea District, Donggala Regency. Methods This type of research is a correlation analytic method with a cross sectional design. The population in this study were all mothers with toddlers aged 24-59 months in Bale Village totaling 188 populations. The number of samples is 53 samples, with the sampling technique proportional random sampling. Data analysis used the chi-square test. The results showed that there was a relationship between mothers' knowledge about exclusive breastfeeding and the incidence of stunting in toddlers aged 24-59 months in Bale Village, Working Area of ​​the Wani Public Health Center, Tanantovea District, Donggala Regency (p-value = 0.001) and there was a relationship between complementary feeding and stunting. in toddlers aged 24-59 months in Bale Village, Working Area of ​​Wani Public Health Center, Tanantovea District, Donggala Regency (p-value = 0.000). The conclusion of this study is that there is a relationship between mother's knowledge about exclusive breastfeeding and giving MP-ASI with the incidence of stunting in toddlers aged 24 -59 months in Bale Village working area of ​​the Wani Health Center, Tanantovea District, Donggala Regency. It is hoped that the Wani Health Center will routinely carry out health counseling and provide nutritious MP-ASI so that it can prevent stunting in toddlers.